Seasonal Dynamics of Methane and Carbon Dioxide Evasion From an Open System Pingo: Lagoon Pingo, Svalbard - Hodson, Andrew Jonathan; Nowak, Aga; Redeker, Kelly Robert; Holmlund, Erik S.; Christiansen, Hanne Hvidtfeldt; Turchyn, Alexandra V. (Frontiers in Earth Science, 2019)
The processes associated with the release of CH4 and CO2 from sub-permafrost groundwaters are considered through a year-long monitoring investigation at a terrestrial seepage site in West Spitsbergen. The site is an open system pingo thought to be associated with the uplift of a former sea-floor pockmark in response to marked isostatic recovery of the coastline following local ice sheet loss over the last 10000 years. We find that locally significant emissions of CH4 and (less so) CO2 to the atmosphere result from a seepage < 1 L s-1 that occurs all year. Hydrological and meteorological conditions strongly regulate the emissions, resulting in periodic outbursts of gas-rich fluids following ice fracture events in winter, and significant dilution of the fluids in early summer by meltwater. Evasion of both gases from a pond that forms during the 100 day summer (45.6 + 10.0 gCH4-C m-2 and 768 + 211 gCO2-C m-2) constitute between roughly 20 and 40% of the total annual emissions (223 gCH4-C m-2 a-1 and 2040 gCO2-C m-2 a-1). Seasonal maximum dissolved CH4 concentrations (up to 14.5 mg L-1 CH4) are observed in the fluids that accumulate beneath the winter ice layer. However, seasonal maximum dissolved CO2 levels (up to 233 mg L-1) occur during late summer. Differences between the δ13C-CH4 composition of the winter samples (average 58.2 +/- 8.01 ‰ (s.d.)) and the late summer samples (average 66.9 +/- 5.75 ‰ (s.d.)) suggest minor oxidation during temporary storage beneath the winter ice lid, although a seasonal change in the methane source could also be responsible. However, this isotopic composition is strongly indicative of predominantly biogenic methane production in the marine sediments that lie beneath the thin coastal permafrost layer. Small hotpots of methane emission from sub-permafrost groundwater seepages therefore deserve careful monitoring for an understanding of seasonal methane emissions from permafrost landscapes.